Carbon Accounting Practices and Financial Sustainability of Oil Producing Companies in Nigeria - Akwaji, Agbor; Effiong, Sunday A; Kubua, Hilary Nkad (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: Examine the effect of carbon accounting practices (scope of emissions, emission sources, emission categories, and reporting boundaries) on financial sustainability of oil-producing companies in Nigeria.Methodology: Survey design, population of 100 staff drawn from five oil-producing companies, census sampling, structured questionnaire, multiple regression analysis.Results: Scope of emissions (β=.129, p=.011), emission sources (β=.290, p=.000), emission categories (β=.144, p=.001), and reporting boundaries (β=.244, p=.000) positively and significantly influenced financial sustainability.Conclusion: Carbon accounting practices significantly enhance financial sustainability of oil-producing companies.Implications: Oil companies should strengthen carbon accounting systems to improve sustainability and stakeholder confidence.
Keywords: Carbon accounting practices; emissions categories; emissions sources; financial sustainability; scope of emissions; scope of reporting boundaries